Management of anemia in children receiving chronic peritoneal dialysis - Borzych-Duzalka, Dagmara; Bilginer, Yelda; Ha, Il Soo; Bak, Mustafa; Rees, Lesley; Cano, Francisco; Munarriz, Reyner Loza; Chua, Annabelle; Pesle, Silvia; Emre, Sevinc; Urzykowska, Agnieszka; Quiroz, Lily; et al. (Journal of the American Society of Nephrology, 2013)
Little information exists regarding the efficacy, modifiers, and outcomes of anemia management in children with CKD or ESRD. We assessed practices, effectors, and outcomes of anemia management in 1394 pediatric patients undergoing peritoneal dialysis (PD) who were prospectively followed in 30 countries. We noted that 25% of patients had hemoglobin levels below target (<10 g/dl or <9.5 g/dl in children older or younger than 2 years, respectively), with significant regional variation; levels were highest in North America and Europe and lowest in Asia and Turkey. Low hemoglobin levels were associated with low urine output, low serum albumin, high parathyroid hormone, high ferritin, and the use of bioincompatible PD fluid. Erythropoiesis-stimulating agents (ESAs) were prescribed to 92% of patients, and neither the type of ESA nor the dosing interval appeared to affect efficacy. The weekly ESA dose inversely correlated with age when scaled to weight but did not correlate with age when normalized to body surface area. ESA sensitivity was positively associated with residual diuresis and serum albumin and inversely associated with serum parathyroid hormone and ferritin. The prevalence of hypertension and left ventricular hypertrophy increased with the degree of anemia. Patient survival was positively associated with achieved hemoglobin and serum albumin and was inversely associated with ESA dose. In conclusion, control of anemia in children receiving long-term PD varies by region. ESA requirements are independent of age when dose is scaled to body surface area, and ESA resistance is associated with inflammation, fluid retention, and hyperparathyroidism. Anemia and high ESA dose requirements independently predict mortality.